2010
DOI: 10.1258/om.2010.090052
|View full text |Cite
|
Sign up to set email alerts
|

Normal vaginal delivery in a patient with autosomal recessive limb-girdle muscular dystrophy

Abstract: Summary:The limb-girdle muscular dystrophies (LGMDs) are a group of genetically determined disorders of skeletal muscle, predominantly affecting the pelvic and shoulder-girdle musculature. The clinical course is variable but steadily progressive. Type 2ALGMD is the most frequent form, accounting for approximately 30% of identified cases. There are few reports of patients with Type 2A LGMD undergoing pregnancy and delivery. This case outlines a successful vaginal delivery in a woman with this condition.Keywords… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…There is one study reporting successful vaginal delivery. 14 Other studies concluded that management of limb-girdle muscular dystrophy should be individualized, as the symptoms vary among patients and spinal anesthesia can be safely used. However, in our study, a case of limb-girdle muscular dystrophy was managed by elective LSCS as per neurologist advice under general anesthesia there were no complications observed during LSCS or in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…There is one study reporting successful vaginal delivery. 14 Other studies concluded that management of limb-girdle muscular dystrophy should be individualized, as the symptoms vary among patients and spinal anesthesia can be safely used. However, in our study, a case of limb-girdle muscular dystrophy was managed by elective LSCS as per neurologist advice under general anesthesia there were no complications observed during LSCS or in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…However, vaginal delivery is possible and has been reported. 11,12 The largest study of obstetric outcomes in women with LGMD includes 22 patients who delivered 29 children. This study reported a high proportion of breech presentations in women with LGMD which was postulated to be related to mobility in pregnancy and wheelchair use.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still controversy about the appropriate options for anaesthesia and analgesia management in SMA patients, as information is limited [25,27]. Similar conclusions are applicable for the heterogeneous group of muscular dystrophies [28][29][30] but due to a variable progression -in comparison to stable SMA III -more women report a negative influence of pregnancy on their muscle disease [31]. The information for FSHD is largely based on a small German and Australian series [31] and a larger American study [32] which yielded conflicting results as to the incidence of operative deliveries and preterm birth rate.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 91%